2016
DOI: 10.1590/0103-6440201602452
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Strength of Weakened Anterior Teeth Associated to Different Reconstructive Techniques

Abstract: This study evaluated the fracture strength of endodontically treated teeth submitted to reconstructive techniques through dynamic and static tests. Forty human anterior teeth were divided into 4 groups (n=10): GNW (non-weakened) -root restored with glass fiber post (GFP), GW -weakened root restored with GFP, GDA -weakened root restored with direct anatomic GFP, and GIA -weakened root restored with indirect anatomic GFP. The teeth were endodontically treated considering that experimental groups (GW, GDA and GIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…Restorative strategies for weakened roots: Systematic review and Meta-analysis of in vitro studies Braz Dent Sci 2019 Jan/Mar; 22(1)…”
Section: S Y S T E M At I C R E V I E Wmentioning
confidence: 99%
See 4 more Smart Citations
“…Restorative strategies for weakened roots: Systematic review and Meta-analysis of in vitro studies Braz Dent Sci 2019 Jan/Mar; 22(1)…”
Section: S Y S T E M At I C R E V I E Wmentioning
confidence: 99%
“…The flowchart of the systematic review is shown in Figure 1. A total of 6 articles [7,10,[19][20][21][22] were included in the analysis. Four articles [7,10,20,21] evaluated CPC, FP, and AP while one [19] presented only CPC and FP groups and one compared FP and AP [22].…”
Section: Descriptive Analysismentioning
confidence: 99%
See 3 more Smart Citations